(untitled) (MATEMATIKA, 2008)
A non-Newtonian pulsatile model of blood flow through multiple stenoses with irregular surfaces is considered. The model chosen is the generalized power law model of blood viscocity where the flow is assumed to be unsteady, laminar, two dimensional and axisymmetric. The governing equations of motion in terms of the viscous shear stress and the boundary conditions in the cylindrical coordinate system are first transformed using a radial coordinate transformation before they are discretized using a finite difference scheme based on central difference approximations on non-uniform grids. The numerical results obtained in terms of blood flow characterictics show that the values of the axial velocity and flow rate in the power-law model are lower while the resistance to flow and the wall shear stress are higher compared to the Newtonian model. These features concur with the general observations of blood flowing through small stenosed arteries. Keywords: Power-law; multi-irregular; stenosed artery; blood flow; non-Newtonian.